2020
DOI: 10.1021/acsaem.9b02026
|View full text |Cite
|
Sign up to set email alerts
|

Interface Fracture Energy of Contact Layers in a Solid Oxide Cell Stack

Abstract: A critical factor for improving the long-term stability/reliability of solid oxide cell stacks is ensuring good adhesion between the stack components. Specifically, ensuring strong adherence between the oxygen electrode and the interconnect is challenging. This work compares the suitability of several materials as contact layers between a La 0.6 Sr 0.4 CoO 3-δ-Ce 0.8 Gd 0.2 O 2 composite oxygen electrode and Mn 1.5 Co 1.5 O 4 or Co coated metallic interconnects. The contact materials were screened based on mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The CuMn foam oxidizes to a conductive spinel at high temperature during the assembly [40], while the Ni foam remains metallic. The two metallic foams adapt to the surface shape of the cell and interconnects, which results in strong interfaces after assembly and oxidation of the cathode side foam [ 41]. The height of a single repeat unit (RU) was 1.4 mm allowing a high power per volume (~3 kW/L without x xxxxx stack end plates assuming 1 W/cm 2 power output, which was achieved with this SOFC generation in earlier studies [25,26]).…”
Section: Stackmentioning
confidence: 85%
“…The CuMn foam oxidizes to a conductive spinel at high temperature during the assembly [40], while the Ni foam remains metallic. The two metallic foams adapt to the surface shape of the cell and interconnects, which results in strong interfaces after assembly and oxidation of the cathode side foam [ 41]. The height of a single repeat unit (RU) was 1.4 mm allowing a high power per volume (~3 kW/L without x xxxxx stack end plates assuming 1 W/cm 2 power output, which was achieved with this SOFC generation in earlier studies [25,26]).…”
Section: Stackmentioning
confidence: 85%
“…The fracture energies of different in-situ sintered perovskite contact layers were determined in Ref. (28). The results for La0.6Sr0.4CoO3-δ (LSC), (La0.8Sr0.2)0.98MnO3-σ (LSM), and LaNi0.6Fe0.4O3 (LNF) are shown in Figure 3.…”
Section: Oxygen Electrode Contact Layermentioning
confidence: 99%
“…Much of the current literature on the mechanical characterization of glass-based seals pays particular attention to fracture toughness, fracture strength, 27 and creep behavior of "pure" glass-ceramic-based seals (i.e., without being interfaced with a metallic interconnect). 28 A small number of studies reported on the shear strength evaluation and have addressed the mechanical behavior of the glass-to-metal seal at the SOC operating temperature (700 • C to 850 • C), as this topic had previously received only minor consideration.…”
Section: Mechanical Characterization Of Glass-to-metal Sealsmentioning
confidence: 99%